2020
DOI: 10.2298/csis190817004w
|View full text |Cite
|
Sign up to set email alerts
|

Damaged buildings recognition of post-earthquake high-resolution remote sensing images based on feature space and decision tree optimization

Abstract: Multi-Agent system has broad application in real world, whose security performance, however, is barely considered. Reinforcement learning is one of the most important methods to resolve Multi-Agent problems. At present, certain progress has been made in applying Multi-Agent reinforcement learning to robot system, man-machine match, and automatic, etc. However, in the above area, an agent may fall into unsafe states where the agent may find it difficult to bypass obstacles, to receive information from other age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The above results confirm that the feature selection using the feature's importance of the tree model which is done by researchers in [34,36,37] is not a good choice. The subset of important features in Table V are the input features when building the decision tree based on the approaches in [34,36,37]. The subset of relevant and independent features in Table VI has confirmed that both subset features have very different elements.…”
Section: Features Importance and Model's Performancesupporting
confidence: 52%
See 1 more Smart Citation
“…The above results confirm that the feature selection using the feature's importance of the tree model which is done by researchers in [34,36,37] is not a good choice. The subset of important features in Table V are the input features when building the decision tree based on the approaches in [34,36,37]. The subset of relevant and independent features in Table VI has confirmed that both subset features have very different elements.…”
Section: Features Importance and Model's Performancesupporting
confidence: 52%
“…The extraction of useful service quality features by using a hybrid model of the Information System and the decision tree to enhance customer satisfaction and loyalty was conducted by Romalt and Kumar [36]. The feature importance of the Decision tree to acquire symbolized sets of damaged buildings as the relevant features only using post-earthquake information was conducted by Wang et al [37]. Finding the feature relevant by identifying and ranking the scores of feature importance generated by three techniques namely impurity-based, permutation-based, and Shap values for building a model to predict breast cancer was done by Mathew [38].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A decision tree (DT) is one of the most intuitively effective classifiers applied in the automatic identification of remote-sensing images. CART is one of the DT classification algorithms, and it is widely used in machine learning and artificial intelligence [14][15][16]. CART is an intelligent algorithm that uses recursive segmentation technology to build a prediction model, which analyzes the relationship between multiple attributes and decisions to generate easy-to-understand rules for prediction [15][16][17].…”
Section: Image Classification By Means Of Machine Learningmentioning
confidence: 99%
“…Timely and accurately acquiring of earthquake damage information of buildings based on remote sensing images is of great significance for post-earthquake emergency response and post-disaster reconstruction [1,2]. Different from common urban scenes, post-earthquake remote sensing images contain rather complex structures and spatial arrangement and earthquake-damaged buildings with diversified patterns are mingled with undamaged buildings, which greatly challenges the abstract representation and feature modeling of earthquake-damaged buildings [3,4]. The automatic detection technology for earthquake-damaged buildings using very high-resolution (VHR) remote sensing images has become a research hotspot in computer vision.…”
Section: Introductionmentioning
confidence: 99%